Multiresolution Expansion and Approximation Order of Generalized Tempered Distributions - Byung Keun Sohn (International Journal of Mathematics and Mathematical Sciences)
Let be the generalized tempered distributions of -growth with restricted order , where the function grows faster than any linear functions as . We show the convergence of multiresolution expansions of in the test function space of . In addition, we show that the kernel of an integral operator provides approximation order in in the context of shift-invariant spaces.